2009
DOI: 10.1111/j.1399-0012.2009.01019.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of enteric‐coated mycophenolate sodium in liver transplant patients with intestinal intolerance caused by mycophenolate mofetil

Abstract: OLT recipients who develop GI side effects caused by MMF can be safely converted to EC-MPS with improvement to their QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
(14 reference statements)
1
13
0
Order By: Relevance
“…A limitation of the current study is that the treatment group is composed of patients with mild to moderate GI symptoms as patients with severe GI disturbances who had previously discontinued MMF were not eligible to participate in this study. This study limitation also occurred in other MMF to EC‐MPS conversion studies (20, 23). A smaller study evaluated eight liver transplant patients who previously discontinued MMF due to GI symptom burden.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…A limitation of the current study is that the treatment group is composed of patients with mild to moderate GI symptoms as patients with severe GI disturbances who had previously discontinued MMF were not eligible to participate in this study. This study limitation also occurred in other MMF to EC‐MPS conversion studies (20, 23). A smaller study evaluated eight liver transplant patients who previously discontinued MMF due to GI symptom burden.…”
Section: Discussionmentioning
confidence: 93%
“…An area of concern with previous EC‐MPS conversion trials is the high rate of discontinuation of EC‐MPS. In one study, 35% of patients discontinued EC‐MPS during the study, although there was significant improvement in the GIQLI in the patients who remained on EC‐MPS (20). Another study showed 28% of patients with no‐change or worsening GI symptoms after conversion to EC‐MPS (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mycophenolate mofetil is primarily absorbed from the stomach; the most common adverse effects associated with MMF are gastrointestinal (GI) disorders, including diarrhoea, abdominal pain, dyspepsia, nausea, vomiting, ulcers and other GI events. EC‐MPS delays the release of MPA into the small intestine, and several studies have reported that it improves the GI tolerability and has better antirejection efficacy . EC‐MPS was introduced to China several years ago and there is limited information about its use in Chinese patients.…”
Section: Introductionmentioning
confidence: 99%